XIV International conference on bionics and applied biophysics - S. O. Mamilov (Біофізичний вісник, 2022)
The article dedicated to the XIV International Conference on Bionics and Applied Biophysics, which took place on October 14–15, 2021 in Kyiv (Ukraine).